Kreativno okolje in uspešnost mladih raziskovalcev - Matelič, Uroš (Družboslovne razprave, 2007)
The results of the study presented in this paper confirm other empirical results obtained via sociological research on the activities of research groups (e.g., Hemlin, Allwood and Martin 2004) that creativity or research productivity is strongly influenced by intra-social factors: autonomy, flexibility, co-operation etc. The analysis presented in the paper confirms that for science at the micro level the relationships among researchers play an important role in scientific performance. This is especially true in the phase of the socialisation and professionalisation of young scientists.
Keywords: Raziskovalci; Researchers; Delovno okolje; Work environment; Creativity; Ustvarjalnost; Znanstveno delo; Scientific work; Scientific community; Znanstvena skupnost; Sociologija znanosti; Sociology of science; Slovenia; Slovenija; mladi raziskovalci